(untitled) (Balthazar, 2021)
Psychoanalysis and Feminism are two fields of Western knowledge that have always been intertwined as well as frequently in conflict. The following dialogue deals with their conjunctions and disjunctions starting from a comment of Paul B. Preciado’s latest work, Je suis un monstre qui vous parle, based on a recent talk of trans-feminist philosopher at the International Conference «Women in Psychoanalysis» at the École de la Cause Freudienne in Paris. Psychoanalysis can act as a practice of dis-adaptation from a series of impositions of the social discourse, and thus be in line with Preciado’s invitation to dis-identify from a system of hetero-patriarchal and colonial norms. However, to what extent this invitation is accepted and practicable by contemporary psychoanalysts on themselves remains in question and is the central issue of this contribution.